Prediction of long-term reverse left ventricular remodeling after revascularization or medical treatment in patients with ischemic cardiomyopathy: a comparative study between SPECT and MRI - Skala, Tomas; Hutyra, Martin; Vaclavik, Jan; Kaminek, Milan; Horak, David; Novotny, Josef; Zapletalova, Jana; Lukl, Jan; Marek, Dan; Taborsky, Milos (The international journal of cardiovascular imaging, 2011)
Patients with ischemic heart disease and depressed left ventricular (LV) ejection fraction (LVEF) develop varying degrees of LV remodeling after cardiac surgical revascularization. Fifty-three patients with stable ischemic heart disease and impaired LV function (LVEF 34.9 ± 4%) were prospectively followed up for 24 months. Thirty-seven patients underwent coronary artery bypass grafting (CABG), 16 patients were treated conservatively. Cardiac magnetic resonance imaging (MRI) and SPECT were performed at baseline and after 12 and 24 months of follow-up. The patients were divided into responders and non-responders depending on the degree of LVEF improvement at 24 months follow-up (>5%-responders). MRI with ≤5 segments with DE/wall thickness ratio (DEWTR) ≥50% predicted LV reverse remodeling with a sensitivity of 86% and a specificity of 75% (AUC 0.81). An MRI finding of ≤2 segments with the DEWTR ≥75% had a corresponding sensitivity of 71% and specificity of 67% (AUC 0.75) while fixed perfusion defect on SPECT <16.5% of LV predicted reverse remodeling with a sensitivity of 64% and a specificity of 69% (AUC 0.64). A preoperative number of segments with the DE/wall thickness ratio of ≥50 and ≥75% obtained by MRI, was found to be a better predictor of left ventricular reverse remodeling than fixed perfusion defect by SPECT. No other MRI or SPECT parameter predicted LVEF improvement at 24 months after CABG.
Keywords: senioři; kardiomyopatie; Stroke Volume; senioři nad 80 let; Cardiovascular Agents; Time Factors; Predictive Value of Tests; Česká republika; výsledek terapie; obnova funkce; Middle Aged; mužské pohlaví; prediktivní hodnota testů; Myocardial Ischemia; Prospective Studies; funkce levé komory srdeční; Tomography, Emission-Computed, Single-Photon; Czech Republic; koronární bypass; tepový objem; koronární angiografie; magnetická rezonanční tomografie; Coronary Angiography; Coronary Artery Bypass; Aged, 80 and over; Magnetic Resonance Imaging; ženské pohlaví; Recovery of Function; Humans; prospektivní studie; Ventricular Remodeling; Cardiomyopathies; kardiovaskulární látky; časové faktory; lidé středního věku; ischemická choroba srdeční; remodelace komor; Female; Aged; jednofotonová emisní výpočetní tomografie; Treatment Outcome; lidé; Male; Ventricular Function, Left